Perancangan Aplikasi Perpustakaan Berbasis Web pada SMK Negeri 1 Rangkasbitung - Salsabilah, Zafira; Yulianti, Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2019)
The school library is one of supporting that could achieve the quality of education. It was because the library could be a source of learning in the school. Management of data processing, lending, and returning of library books could take a lot of fees and times. It was because using a ledger. Besides, the students having difficulties in order to get the books. It was because there is no technology information that provide the search engine toward a books. This research was focus on the library information system. The objective of this research were to facilitate officer in managing the library data and to make the students easy to find the books. This library application is website-based which is develop by using the PHP as programming language while MySQL as database management system. The method that used to conduct the data were structured interview, literature study, and observation which regard to the school library in making a library application. This study gives the result in the usability aspect the percentage is 79,5%, its mean that the library application could facilitate officer in processing data collection, borrowing and returning library books, moreover, the students could search the book easily.